Short Communication: Botanical assessment and conservation status of medicinal plants in mountain range of Malinao Albay, Philippines - TERESA HAIDE R. BELGICA; MARLON D. SUBA; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Belgica THR, Suba MD, Alejandro GJD. 2024. Short Communitation: Botanical assessment and conservation status of medicinal plants in mountain range of Malinao Albay, Philippines. Biodiversitas 25: 1413-1419. Mount Malinao in Albay Province, Philippines is considered to harbor a diverse array of medicinal plants that are invaluable to local communities and have potential global significance. Despite its ecological importance and diverse floral and faunal species, there is a lack of an extensive profile of medicinal flora in the area. Therefore, this study aims to catalog and evaluate the conservation status of these medicinal plants for conservation strategies and sustainable management. Sampling took place from April to June 2016 in the lower agroforest with diverse agricultural resources with elevation of 51 to 300 meters above sea level. The comprehensive inventory of medicinal plants involved a combining field surveys, available ethnobotanical studies, ecological assessments, and thorough research, resulting in the identification of 74 species of medicinal flora from 38 families and 72 genera. Based on the International Union for Conservation of Nature (IUCN) criteria, three species were identified as Data Deficient (DD), 24 species were categorized as Least Concern (LC), and 47 were marked as Not Evaluated (NE). Additionally, 72 medicinal plants were identified as Non-Endemic, while two species were considered endemic, including Canarium ovatum Engl, and Voacanga globosa (Blanco) Merr. By understanding the ecological importance and cultural significance of these medicinal plants, this assessment provides a foundation for conservation efforts aimed at maintaining biodiversity, supporting local livelihoods, and safeguarding traditional knowledge for future generations.